2005
DOI: 10.1111/j.1600-6143.2005.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Murine Obliterative Airway Disease

Abstract: Lung and heart-lung transplantation are effective treatments for many diseases unresponsive to other therapy. However, long-term survival of recipients is limited by the development of obliterative bronchiolitis (OB). In this study, microarray analysis of a heterotopic mouse model of obliterative airway disease (OAD) was used to test the hypothesis that the expression and patterns of genes will correlate with specific changes in tracheal tissue developing a response to allotransplantation and the infiltrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…We found that changes in gene expression originated directly from the transplanted lung that showed histologic signs of CR at 90 days, as described in rats, 16,17 and could be compared with other microarray studies. [8][9][10] In this model of inbred rats, we detected native expression of genes originally involved in CR, which has not been observed in previous studies, where immunosuppressants modulated the response to rejection.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…We found that changes in gene expression originated directly from the transplanted lung that showed histologic signs of CR at 90 days, as described in rats, 16,17 and could be compared with other microarray studies. [8][9][10] In this model of inbred rats, we detected native expression of genes originally involved in CR, which has not been observed in previous studies, where immunosuppressants modulated the response to rejection.…”
Section: Discussioncontrasting
confidence: 42%
“…In our study, Tgfb was the second most prominent up-regulated pathway and Tgfb1 mRNA was significantly increased, suggesting that this pathway has a major role in the pathogenesis of AR and CR, but has not been described in previous microarray studies. 8,9 These findings could have clinical relevance since it has been reported that Tgfb expression is increased in patients with BOS, even prior to the onset of airflow obstruction, 10 and Tgfb is able to directly induce pulmonary fibrosis. 24 The main activities of Tgfb1 are cell growth inhibition and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thymosin beta-4 enhances the survival of transplanted mesenchymal stem cells for cardiac repairby reducing apoptosis [17]. In addition, gene expression profiling from a murine model of obliterative bronchiolitis demonstrated an increase in thymosin expression [18]. These studies suggest that thymosin may promote cellular and tissue growth in the development of BOS.…”
Section: Go Biological Process P-value Genementioning
confidence: 83%
“…Although there is an open debate on whether the measures contained in the QC reports can identify quality problems, QC reports are commonly used to assess the quality of microarrays (Finkelstein, 2005;Landea et al, 2005). One common practice is to compare the values of each measure against ad hoc thresholds.…”
Section: Introductionmentioning
confidence: 99%